Using Active Learning in Criminal Justice: Twenty-Five Examples - Robinson, Matthew B. (Journal of criminal justice education, 2000)
Active learning strategies may overcome the weaknesses of the traditional lecture approach. This paper outlines some of the main strengths and weaknesses of the lecture approach and reports research which illustrates why active learning strategies should be used in the classroom. The paper concludes with a presentation of twenty-five active learning strategies to be used in the criminal justice classroom, along with a discussion of how these strategies meet the goals of higher education